30 INTANGIBLE ASSETS ACCOUNTING PHRASES (ANNOTATED) - Valdivia Ramos, Román Arturo (2013)
This research mainly discusses the intangible assets of a company and its relationship with the Accounting Science. Traditional accounting is not yet able to record intangible assets, therefore, a drastic and substantial change in its procedures and regulations is necessary. Every day that passes, for a company or organization, intangible assets or increase its value up, whereas tangible as time goes on assets, are lost . There is an inverse relationship. On the other hand, accounting is dynamic, changing, therefore, must be adapted to the needs and requirements of the company, even at the cost of changing paradigms deeply rooted in many counters, instead of interpreting the business, are “more interested in perpetuating a practice that leaves them some dividends . “ They have forgotten that the current trend is to make a completely different accounts of both form and substance . We are optimistic, therefore, we are convinced that the current accounting (not the future), will create models and systems to record and accounting for intangible assets.